Karnaval Sound Horeg as Public Harm: A Maqāṣid al-Sharī‘ah and Indonesian Legal Analysis - Achmad Faiqur Rijal; Selah Nurul Ma’rifah (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines Karnaval Sound Horeg as a contemporary cultural phenomenon in Indonesia that functions as public entertainment while simultaneously generating social and environmental concerns. The excessive use of high-volume sound systems often leads to noise pollution, disruption of public order, and ethical issues regarding the limits of cultural expression. This research aims to analyze Karnaval Sound Horeg from the perspectives of Islamic law and Indonesian positive law, with a focus on the concept of public harm (mafsadah). This research employs qualitative library research. Data were collected from classical and contemporary fiqh literature, statutory regulations, and relevant academic sources. The analysis is conducted through normative and comparative approaches between Islamic legal theory and Indonesian environmental law. Previous studies have mainly focused on the sociological and cultural dimensions of Sound Horeg, such as identity formation and social symbolism. However, there is limited scholarly attention to its normative legal evaluation, particularly using an integrated framework of maqāṣid al-sharī‘ah and Indonesian positive law. This study addresses that gap by providing a legal-ethical analysis of Sound Horeg through the concept of public harm and environmental regulation, thereby contributing both to Islamic legal discourse and policy-oriented discussions on public noise control.The findings indicate that, in Islamic law, excessive sound usage constitutes harmful conduct categorized as laghw and tabdhīr, both of which are discouraged due to their negative social impacts. From the perspective of Indonesian positive law, such practices violate environmental noise regulations as stipulated in Law No. 32 of 2009 on Environmental Protection and Management and Ministerial Decree No. 48 of 1996. The study concludes that both legal systems share a normative commitment to safeguarding public welfare and preventing social harm.